2019
DOI: 10.31235/osf.io/yt4xd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organizational Learning Orientation and Sustainable Competitive Advantage: Towards More Accountable Government-Linked Companies

Abstract: Government-Linked Companies (GLCs) are expected to show competitive performance in order to reflect the accountability of taxpayers’ money. Therefore, this study is an attempt to assess the status of the current level of organizational learning orientation among the Government-Linked Companies (GLCs) in Malaysia. This study collected primary data based on a set of questionnaire survey among 134 executives and managers of GLCs in Malaysia. The data were collected based on opinions of the ten factors of organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…(2017) investigated the relationship between organizational learning and competitive advantage in the context of Taiwan and found the contributory role of organizational learning into a firm competitive advantage. In another study, the authors found a positive and significant relationship between organizational learning and competitive advantage (Zulkarnain et al, 2016). Therefore, above discussed literature show the contributory role of organizational learning in firm competitive advantage against competitors, hence organizational learning can sustain the competitive advantage in the context of Iraq, where low competition recorder.…”
Section: Organizational Learning and Competitive Advantagementioning
confidence: 84%
See 1 more Smart Citation
“…(2017) investigated the relationship between organizational learning and competitive advantage in the context of Taiwan and found the contributory role of organizational learning into a firm competitive advantage. In another study, the authors found a positive and significant relationship between organizational learning and competitive advantage (Zulkarnain et al, 2016). Therefore, above discussed literature show the contributory role of organizational learning in firm competitive advantage against competitors, hence organizational learning can sustain the competitive advantage in the context of Iraq, where low competition recorder.…”
Section: Organizational Learning and Competitive Advantagementioning
confidence: 84%
“…There are many researchers found the critical factors which constitute a contributing part in sustainable competitive advantage such as export business strategy (Leonidou et al, 2015); marketing capabilities (Tan & Sousa, 2015); human resource management practices (Albrecht et al, 2015); dynamic capabilities (Li & Liu, 2014); information technology and knowledge management (Mao et al, 2016); employee empowerment (Ghosh, 2013) and organizational learning (Zulkarnain et al, 2016). Yet, Francescato and Aber (2015) stated that empowerment is (a) to offer the opportunity for advancement, (b) to access to information, (c) to access to funding, and (d) the opportunity to develop and discover.…”
Section: Introductionmentioning
confidence: 99%
“…Some GLCs have not been able to create any value and have been experiencing poor performance namely companies like the Proton Holding Berhad and the Malaysian Airline System. Thus, the GLCs have to try harder with new initiative to create value in order to address the government's needs and expectations while increasing and adding value to their services, products, and enterprise performance (Aziz et al, 2015a,b,c;Said et al, 2015Said et al, , 2016aLawler & Mohrman, 2013;Zulkarnain et al 2016). According to Khazanah (2014), starting from 2015, GLCs must improve and work on their creation of value by concentrating on sustainability practices and the execution.…”
Section: Introductionmentioning
confidence: 99%